Amyloid-β Peptide (Aβ) Neurotoxicity Is Modulated by the Rate of Peptide Aggregation: Aβ Dimers and Trimers Correlate with Neurotoxicity - Hung, Lin Wai (J Neurosci, 2008)
Alzheimer's disease is an age-related neurodegenerative disorder with its toxicity linked to the generation of amyloid-β peptide (Aβ). Within the Aβ sequence, there is a systemic repeat of a GxxxG motif, which theoretical studies have suggested may be involved in both peptide aggregation and membrane perturbation, processes that have been implicated in Aβ toxicity. We synthesized modified Aβ peptides, substituting glycine for leucine residues within the GxxxG repeat motif (GSL peptides). These GSL peptides undergo β-sheet and fibril formation at an increased rate compared with wild-type Aβ. The accelerated rate of amyloid fibril formation resulted in a decrease in the presence of small soluble oligomers such as dimeric and trimeric forms of Aβ in solution, as detected by mass spectrometry. This reduction in the presence of small soluble oligomers resulted in reduced binding to lipid membranes and attenuated toxicity for the GSL peptides. The potential role that dimer and trimer species binding to lipid plays in Aβ toxicity was further highlighted when it was observed that annexin V, a protein that inhibits Aβ toxicity, specifically inhibited Aβ dimers from binding to lipid membranes.